СИЛА ТЯЖЕСТИ И "АНТИГРАВИТАЦИОННЫЕ" ПРОЦЕССЫ В ФОРМИРОВАНИИ РЕЛЬЕФА ЗЕМЛИ - Агафонов Б.П. (My University, 2004)
nlike the traditional opposition of endogenous and exogenous processes in the relief formation author contradistinquishes the processes running dew to gravity and against it. The latter two types include endogenous as well as exogenous processes. The Processes submitting to gravity comprise the downcast lithoflow, “antigravitational” processes overcome gravity and direct upward. Special attention is paid to out-of-the-way mechanism of waves-wind sand outflow from the large waters onto the slopes covered with thick forest. Some other examples of “antigravitational” processes are given; the conclusion is drawn that the landforms in every certain region are governed by the ratio of these two types of processes.
Keywords: 551.4.04